1990
DOI: 10.1007/bf00174632
|View full text |Cite
|
Sign up to set email alerts
|

Local cerebral glucose utilization in the neocortical areas of the rat brain

Abstract: The neocortex of the rat brain can be subdivided into regions of different local cerebral glucose utilization (LCGU). However, only a few neocortical areas can be delineated by differences in mean LCGUs between neighbouring areas. These area borders correspond exactly with cytoarchitectonically defined borders found in adjacent Nissl-stained preparations. On the other hand, nearly all of the architectonically defined area borders are also recognizable in the LCGU pictures, if differences in laminar distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…The hypothesis is that in LTP NO liberated from CAI pyramidal cells acts as a retrograde messenger to alter the presynaptic membrane in such a way as to facilitate neurotransmitter release. In the present study, 1CMR,,, in the molecular layer of hippocampus, which is composed of both the molecular-lacunosum layer of the hippocampal CAI -3 and the external limb of the dentate gyrus (Wree et al, 1988), did not show any changes following inhibition of brain NO synthase activity. In- 1.…”
Section: Discussioncontrasting
confidence: 47%
“…The hypothesis is that in LTP NO liberated from CAI pyramidal cells acts as a retrograde messenger to alter the presynaptic membrane in such a way as to facilitate neurotransmitter release. In the present study, 1CMR,,, in the molecular layer of hippocampus, which is composed of both the molecular-lacunosum layer of the hippocampal CAI -3 and the external limb of the dentate gyrus (Wree et al, 1988), did not show any changes following inhibition of brain NO synthase activity. In- 1.…”
Section: Discussioncontrasting
confidence: 47%
“…If the higher Glu concentration in the mPFC voxel reflects higher regional glutamatergic activity, the energy consumption rate should be higher in the mPFC than in the pCG. Previous autoradiograph studies, however, reported similar cerebral glucose utilization rates (rCGU) in the two regions . The explanation for this apparent discrepancy probably lies in the fact that regional rCGU variations are not necessarily in parallel with the variations in regional cerebral metabolic rate of glucose oxidation (CMR glc(ox) ).…”
Section: Discussionmentioning
confidence: 87%
“…Previous autoradiograph studies, however, reported similar cerebral glucose utilization rates (rCGU) in the two regions. 50 The explanation for this apparent discrepancy probably lies in the fact that regional rCGU variations are not necessarily in parallel with the variations in regional cerebral metabolic rate of glucose oxidation (CMR glc(ox) ). For example, rCGU measured with autoradiography was reported to be 45% higher in the temporal cortex than in the parietal cortex in rats, 51 while CMR glc(ox) measured with ex vivo 13 C-MRS was 17% lower in the temporal cortex than in the parietal cortex.…”
Section: Glu Concentration and Energy Metabolismmentioning
confidence: 99%
“…As the left CMRglc values of many hippocampal layers and areas turned out to be higher than the right CMRglc values (analyzed with the t test for matched pairs) and the lesion-induced effects were principally the same in both hemispheres, only the results of the left hemisphere are presented in detail. Moreover, we published the results of the left hemisphere before (Wree et al, 1988). For each of the brain regions, the CMRglc values of the four experimental groups were compared by one-way analysis of variance (ANOV A).…”
Section: Discussionmentioning
confidence: 99%